Bulgarian Newspapers Between Agony and Renaissance – Audience’s Attitude, Habits and Expectations - Simeonova, Lora (Media and Language, 2021)
Who does (not) read newspapers today and why? Is the Bulgarian press doomed or its Renaissance is achievable – albeit online? The present study tries to answer these questions analyzing the attitude, habits and expectations of the audience. The results demonstrate the dimensions of the newspaper crisis – loss of readers, “dawn” of the reading ritual, young public alienation and problematic mediamorphosis. At the same time, data outlines possible positive scenario for the Bulgarian newspapers – which requires emphasis on quality media content and user experience in the digital environment.